Uji Aktivitas Antioksidan Ekstrak Etanol Sirih Cina (Pepperomia pellucida) dengan Metode DPPH (1,1-diphenyl-2-picrylhydrazyl) - Ni Putu Refina Dharma Yanti; Ni Putu Putri Cahya Anggreni; Kadek Ayu Puspa Pratiwi; Ni Nyoman Wahyu Udayani; Ketut Agus Adrianta (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Free radicals play an important role in pathological processes and tissue damage. The pepperomia pellucida plant is often used as a traditional medicine, known to have antibacterial, anti-inflammatory, hypoglycemic, antifungal, antimicrobial, anticancer, antioxidant, antidiabetic and antihypertensive activity. Excessive free radicals can attack vulnerable compounds such as lipids and proteins which can cause various diseases. The Pepperomia pellucida plant is a plant that contains secondary metabolites such as alkaloids, flavonoids, saponins, tannins and steroids. The aim of this research was to determine the antioxidant activity of Pepperomia pellucida ethanol extract with variations of 70% and 80%. The results of the DPPH (1,1-diphenyl-2-picrylhydrazyl) ethanol extract of Pepperomia pellucida extract in the 70% variation showed IC50 = 24.50981 ppm and the 80% variation showed IC50 = 30.49915 ppm. Based on the research results of the two variations of ethanol, it was found that the best IC50 result was Pepperomia pellucida ethanol extract with a variation of 70% because it had a smaller IC50 result than the 80% ethanol variation, namely with an IC50 figure = 24.50981 ppm. The results of the phytochemical screening of the ethanol extract of pepperomia pellucida indicated positive results from several tests, namely alkaloids, flavonoids, steroids, saponins and tannins.